Storage root nutrient and yield enhancement in sweet potato variety vitato using empty fruit bunch compost and hexaconazole - Borhan Abdul Haya @ Yahya; Mohd Yusoff Abdullah; Nur Kharunisa Tajarudin (ANSI net, 2016)
Bacterial wilt is a major ginger disease in Sabah after rhizome rot. The disease has affected the production of ginger in Sabah since 2005. In this study, the ginger plants with foliar symptoms (yellowing and wilting), collected from six ginger-growing areas in the Tambunan and Ranau districts, were observed to have signs of bacterial pathogen (i.e., rhizome rot and bacterial ooze). A total of 19 bacterial strains were isolated, and all of the isolates were characterised as rod-shaped and Gram-negative by Gram-staining and potassium hydroxide test and microscopic examination. MALDI-TOF analysis identified six species from the isolates: Enterobacter cloacae complex (57.9%), Ralstonia pickettii (10.5%), Agrobacterium tumefaciens (10.5%), Bacillus pumilus (10.5%), Stenotrophomonas maltophilia (5.3%) and Serratia marcescens (5.3%). In pathogenicity test, E. cloacae, which constituted most of the isolates, induced mild rot symptoms (discoloration) on ginger rhizome slices, but no disease symptoms were produced in ginger plants. Further studies on the interaction of E. cloacae with other isolated species are required to confirm the causes of ginger wilt disease in Sabah, Malaysia.